Recherches sur les madragues marines et les perspectives de l'applications des résultats dans la production - Elefteriu, Romeo; Jelescu, Nicolae; Cociașu, Adrian (Cercetări Marine - Recherches Marines, 2026)
The paper describes a new type of so-called "combined" set net with trap, designed, manufactured and tested by the Romanian Marine Research Institute of Constanta, during 1970-1971. The paper presents the advantages of the new type of set net with trap regarding its operation, catch and cost, all compared to the Industrial sets net with trap as witness- These elements are in favor of the adoption of the type of set net with trap in industrial fishing.